Analysis of Influenced Factors on Consumer Behaviour: The Demand of Chicken Egg’s in TebingTinggi City - Siti Hanifah Putri; Armyn Hakim Daulay; Hamdan .; Edhy Mirwandhono; Tri Hesti Wahyuni (Universitas Sumatera Utara, 2018)
The purpose of this study were to identify factors that affect the demand forchicken eggs and to find out the correlation of factors that affect consumer behavior inpurchasing chicken eggs in Tebing Tinggi City. The research used primary data obtainedfrom questionnaires or interviews. The research method was multiple linear regressionmethods, spearman rank correlation and contingency correlation.The results showed that the price of chicken eggs and the income had real effect to thedemand for chicken eggs in the area of research. The result of spearman rank correlation andthe contingency correlation showed that there was a real correlation between the incomewith a consumer behavior in purchasing chicken eggs, while the age, employment, andnumber of consumer dependents, did not show real correlation with consumer behavior inpurchasing chicken eggs.